E-010 Relation between brain natreuretic peptide and delayed cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage. (22nd July 2019) - Kaur, G; Damodara, N; Gupta, R; Patel, V; Santarelli, J; Gandhi, C; Al-Mufti, F
Abstract : Background: Immune regulation and inflammation is implicated in the development of delayed cerebral ischemia (DCI) in patients with aneurysmal subarachnoid hemorrhage (aSAH). BNP is implicated in fluid dysregulation and inflammation in critically-ill patients. We explored the association between BNP levels and development of DCI in patients with a SAH. Methodology: Patients were enrolled from the Neurological Intensive Care Unit between 2006 and 2015 in the SAH Outcomes Project, a single center, prospective, observational cohort study. Demographic data, treatment and outcomes, and BNP levels at admission and through the hospital admission were noted. Results: In the 149 patients included in the analysis, 79 developed DCI during their hospital course. Significantly higher number of patients in the DCI group had external ventricular drain (EVD) placements (p=0.008). The DCI group also had significantly higher rates of rebleeding and hydrocephalus. In the logistic regression analysis between BNP levels and DCI, there is a significant association with admission BNP and DCI (OR-1.002, 95%CI 1.00–1.004, p=0.017), DCI and highest BNP (OR 1.001, 95%CI-1.001–1.002, p=0.002), and change in BNP with change in time (OR 1.006, 95%CI 1.002–1.01, p=0.002). The ROC curve analysis for DCI based on BNP showed that the highest BNP level during hospital admission (AUC 0.78) was a stronger predictor than the change in BNP over time (AUC 0.776) or the admission BNP (AUC 0.632). Conclusion: There is a significant association between the BNP level and the risk of developing DCI. This increased risk for DCI is associated not only with higher baseline BNP values (admission BNP) but also with the highest BNP level attained during the hospital course as well as the rapidity of change or increase in BNP over time. Hence, BNP values may help to identify SAH patients at high risk of cardiac morbidity and facilitate appropriate triaging. Disclosures: G. Kaur: None. N. Damodara: None. R. Gupta: None. V. Patel: None. J. Santarelli: None. C. Gandhi: None. F. Al-Mufti: None.